RobotX challenge 2022: development of surface vehicle's shooting system of ball - Tan, Immanuel Aik Jin (Nanyang Technological University, 2023)
This paper, titled “Development of Surface Vehicle’s Shooting System of Ball” is based on the Maritime RobotX Challenge. The challenge is an international competition, where students are invited to compete to build an unmanned surface vehicle (USV) on the Wave-Adaptive Modular Vessel.